Nucleotide Structure and Characterization of the Murine Blood Coagulation Factor VII Gene - Idusogie, Esohe; Rosen, Elliot D; Carmeliet, Peter; Collen, Desire; Castellino, Francis J (Thrombosis and Haemostasis, 1996)
The gene encoding murine coagulation factor VII (fVII) has been cloned. Seven introns and eight exons are present, with the introns positioned as splice junctions between the major domain units of the protein. A total of 11,748 bp of the gene was sequenced, and included 1,077 bp of a 5’-flanking region, in which several high probability binding sites for liver transcription factors were present, as well as a CCAAT sequence and possible GC boxes. Primer extension analysis revealed that the major transcription start site was positioned only 9 residues upstream of the ATG initiation codon, thus providing a very short 5’-untranslated region of the gene. The sequence of the CAP site in the murine fVII gene matched exactly the consensus eukaryotic sequence. A total of 1,484 bp of 3’-flanking nucleotides included a probable polyadenylation site (ATTAAA) and an appropriately positioned downstream consensus sequence (AGTGTTTC) for the efficient formation of a 3’ terminus of mRNA. These results indicate that all elements are present for liver-based transcription of the gene for murine factor VII. The sequence and restriction endonuclease map of this gene will facilitate construction of fVII deficient mice and mice containing mutant fVII genes.